Implementasi Kurikulum Merdeka di PAUD Al-Islam Riyadhul Irfan Kadungora Sebagai Sekolah Penggerak Angkatan III - Siti Aliyah; Shelli Pratiwi; Aeni Latifah (Institut Madani Nusantara, 2024)
This study is motivated by the interest of researchers' interest in the implementation of Merdeka curriculum in PAUD Al-Islam Riyadhul Irfan Kadungora as a Sekolah Penggerak Angkatan III. The purpose of this research is to know the the implementation of Merdeka curriculum in PAUD Al-Islam Riyadhul Irfan Kadungora as a Sekolah Penggerak Angkatan III. his research uses a qualitative, qualitative approach with descriptive type. Data collection techniques in this study data collection techniques in this study are observation, interviews and documentation, then the data analysis techniques used are data reduction, data analysis, and data analysis. The data analysis techniques used are data reduction, data presentation and verification. The results of this study indicate that: Implementation of Merdeka curriculum in PAUD Al-Islam Riyadhul Irfan Kadungora as a Sekolah Penggerak Angkatan III Well done, but there are obstacles from two factor is internal and external factors. The internal factor is educators and educational staff are not yet optimal for use the Platform Merdeka Mengajar application and their albility not yet fully based for a need child. Besides that external factor is the realisations for activity not according to the predetermined schedule.